PHYSICAL PRACTICES BETWEEN MODERN SOCIETY AND NATURAL ENVIRONMENT (GYMNASIUM, 2009)
This essay, tries to analyze the changes of physical practices in our society regarding tthe relationbetween modern society and natural environment. I intend to link the characteristics of this society withsome particular type of physical practice, the one related to the nature.A few introductory ideas aime to explain how the changes, mainly economic and social, whichoccurred from mid-century, have brought major changes in the way of understanding the world. Thesechanges, in the design and lifestyles of people have influenced every one of the social fields. From this basis,my interest is to show the relationship between these social changes, and the physical practices in naturalenvironment.